Vocabulaire périglaciaire bilingue - Hamelin, Louis-Edmond; Clibbon, Peter (Cahiers de géographie du Québec, 1962)
A considerable lack of agreement exists, particularly between French and English-speaking geomorphologists, on the precise use of many periglacial terms, and up to the presenty there bas been little correlation of the periglacial terminology of these two languages. Accordingly, the authors have prepared a bilingual glossary of 900 periglacial terms in an attempt to eliminate some of this confusion.Many of the problems encountered in the preparation of this glossary result from different conceptions of the terms « periglacial » and « périglaciaire ». Periglacial studies are generally considered to involve analyses of permanently frozen ground, patterned ground and frost-shattering, whereas the term « périglaciaire »refers to the systematic study of all « cold »processes (except those associated with glacier ice) and their resultant phenomena. The term thus includes, amongst other things, gelifraction, gelifluction, geliturbation, fluvioperiglacial action, effect of sea, lake, river and ground ice, windwork in areas of cold climate, action of snow, and chemical erosion by meltwater.